2007
DOI: 10.5194/acpd-7-289-2007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Secondary aerosol formation from atmospheric reactions of aliphatic amines

Abstract: Abstract. Although aliphatic amines have been detected in both urban and rural atmospheric aerosols, little is known about the chemistry leading to particle formation or the potential aerosol yields from reactions of gas-phase amines. We present here the first systematic study of aerosol formation from the atmospheric reactions of amines. Based on laboratory chamber experiments and theoretical calculations, we evaluate aerosol formation from reaction of OH, ozone, and nitric acid with trimethylamine, methylami… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
175
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(186 citation statements)
references
References 46 publications
8
175
2
1
Order By: Relevance
“…Besides, TMA can also participate in the formation of secondary organic aerosol. Several studies have shown that gas-phase TMA could form non-salt organic aerosol products through reaction with oxidizing agents such as O 3 , OH, and NO 3 radical (Murphy et al, 2007;Silva et al, 2008). The relative importance of atmospheric behaviors of TMA in different regions is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, TMA can also participate in the formation of secondary organic aerosol. Several studies have shown that gas-phase TMA could form non-salt organic aerosol products through reaction with oxidizing agents such as O 3 , OH, and NO 3 radical (Murphy et al, 2007;Silva et al, 2008). The relative importance of atmospheric behaviors of TMA in different regions is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al (2002) suggested that the presence of the TMA within aqueous surface on particles would promote the accumulation of sulfate and nitrate (R2 and R3). TMA also has the potential to undergo gas phase acidebase reactions (R4) with gaseous acids (e.g., HCl, HNO 3 and H 2 SO 4 ) mimic ammonia to form inorganic salts (Angelino et al, 2001;Murphy et al, 2007). Additionally, heterogeneous reaction between gas-phase TMA and acid (R5) could take place as well.…”
Section: Possible Formation Mechanism Of Particulate Tmamentioning
confidence: 99%
See 1 more Smart Citation
“…12 Amines observed in Marshall Field Site, Colorado (2007), 13 North Boulder, Colorado (2009), and Atlanta, Georgia (2009) 14 have also been confirmed to play the same role in NPF events. 12 In laboratory studies, NPF was observed when amines were added into a smog chamber or flow tube reactor containing a certain concentration of nitric acid, 15 sulfuric acid, 16 or methanesulfonic acid (MSA). 17,18 Density functional theory (DFT) calculations indicated that amine molecules act as cluster stabilizers for nucleation precursors, 19,20 and therefore promote nuclei formation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…34 It has also been found that significant nonsalt organics contributed to the secondary organic aerosol (SOA) from ozone oxidation and photooxidation of TMA and TEA. 15 Particulate amines and secondary oxidation products from amines in the particle phase are associated with adverse aerosol health impacts. For example, concentrations of 20 mL·m −3 trimethylamine were found to found to irritate the mucous membranes and eyes.…”
Section: ■ Introductionmentioning
confidence: 99%